Car Park Management System based on Arduino - Alhaji, Dana; Madi, Nada; Alaqraa, Heba (My University, 2017)
This graduation project represents a simple smart system. Using Arduino controller, this system made for the indoor parking to provide an easy and simple way to park which will reduce traffic save time and gaz. Subscriber customers can benefit from the system. Payment is done by prompt system. The system designed for two types of customers: First is the default customer, who depends on the system to find the closest empty place in the park for small amount of money discounted from the customer visa card number stored in the customer’s database. For this type of customer an extra service has been provided versus extra money which gives them the right to choose instantaneously a specific temporary empty place in the park. Second type: is the VIP customer, this customer chooses a specific permanent place and this place is reserved for this person no one else can park in their place.